Spreading Knowledge in Medical Informatics: the Contribution of the Hospital Italiano de Buenos Aires - de Quiros, F. Gonzalez Bernaldo; Luna, D.; Otero, P.; Baum, A.; Borbolla, D. (Yearbook of Medical Informatics, 2009)
Medical Informatics (MI) is an emerging discipline with a high need of trained and skillful professionals.Objective To describe the educational experience of the Department of Health Informatics of the Hospital Italiano de Buenos Aires.Methods A descriptive study of the development of the Medical Informatics Residency Program (MIRP) and the e-learning courses related to medical informatics.Results A four-year MIRP with 15 rotations was started in 2000, and was awarded national educational accreditation. Eight residents have been fully trained and their main academic contributions are shown in this study.The e-learning courses related to medical informatics (Healthcare Management, Epidemiology & Biostatistics, Information Retrieval, Computer Literacy started, 10x10 Spanish version and HL7 introductory course) started in 2006 and were followed by more than 2266 students from all over the world, with an increase trend in foreign students.Conclusions These educational activities have produced skilled human resources for the development and maintenance of the health informatics projects at our Hospital. In parallel, the number of students trained by e-learning continues to increase, demonstrating the worldwide need of knowledge in this field.
Keywords: Biomedical informatics; education; health information systems; healthcare workforce